MUHAMMAD: LELAKI PENGGENGGAM HUJAN SEBAGAI ‎SUMBER BELAJAR AFEKTIF SEJARAH DAN ‎KEBUDAYAAN ISLAM - Firdaus, Muhammad Iqbal; Junanah, Junanah Junanah (Ta'allum: Jurnal Pendidikan Islam, 2020)
Abstract: This study aims to describe the findings related to the affective aspects of the novel “Muhammad: Lelaki Penggenggam Hujan” by Tasaro GK. This is motivated by the facts which show that learning of Islamic History and Culture is still mostly done based on cognitive aspects alone. This is certainly not in line with the characteristics of these learning which not only include the development of the cognitive aspects of students, but also demands empowerment in the affective and psychomotor aspects. So that one alternative problem solving that can be offered is to use novels as a source of affective learning. The discussion in this study was carried out with a content analysis consisting of four steps; data procurement, data reduction, data analysis, and inference. The results of data analysis show that there are various forms of simulations on the level of affective aspects in the novel “Muhammad: Lelaki Penggenggam Hujan”.